2004
DOI: 10.1002/jbm.a.30047
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of a novel electrically conductive polypyrrole/poly(D,L‐lactide) composite and polypyrrole‐coated poly(D,L‐lactide‐co‐glycolide) membranes

Abstract: This study evaluated the in vivo biocompatibility and biodegradation behavior of a novel polypyrrole (PPy)/poly(D,L-lactide) (PDLLA) composite and PPy-coated poly(D,L-lactide-co-glycolide) membranes. Test membranes were implanted subcutaneously in rats for 3-120 days. The biocompatibility was assessed by quantifying the alkaline and acid phosphatase secretion, the immunohistochemical staining of the ED-2-positive macrophages, and the histology at the tissue/material interface. The degradation was investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 19 publications
(26 reference statements)
4
50
0
Order By: Relevance
“…The selection of the dopant counterions during the synthesis of electroactive polymers has an effect on the biocompatibility of the electroactive polymer (PPy) in vitro, with high molecular weight dopants (typically polyanions such as polystyrene sulfonate) being attractive because they will not readily leach from the polyelectrolyte complex formed with the (typically) polycationic PPy [18][19][20][21]. Interestingly, in vivo studies of electroactive scaffolds have been carried out and histological analyses of tissue surrounding polypyrrole-based tissue scaffolds implanted subcutaneously or intramuscularly in rats reveal immune cell infiltration comparable to FDA-approved poly(lactic acid-co-glycolic acid) [22] or FDA-approved poly(D,L-lactide-co-glycolide) [23]. Likewise, no significant inflammatory response was observed with polypyrrole-based sciatic nerve guidance channels implanted in rats after 8 weeks [24], polypyrrole-coated electrodes in rat brains after 3 or 6 weeks [25], or most pertinently, polypyrrole-based tissue scaffolds implanted in the coronary artery of rats after 5 weeks [26].…”
Section: Introductionmentioning
confidence: 94%
“…The selection of the dopant counterions during the synthesis of electroactive polymers has an effect on the biocompatibility of the electroactive polymer (PPy) in vitro, with high molecular weight dopants (typically polyanions such as polystyrene sulfonate) being attractive because they will not readily leach from the polyelectrolyte complex formed with the (typically) polycationic PPy [18][19][20][21]. Interestingly, in vivo studies of electroactive scaffolds have been carried out and histological analyses of tissue surrounding polypyrrole-based tissue scaffolds implanted subcutaneously or intramuscularly in rats reveal immune cell infiltration comparable to FDA-approved poly(lactic acid-co-glycolic acid) [22] or FDA-approved poly(D,L-lactide-co-glycolide) [23]. Likewise, no significant inflammatory response was observed with polypyrrole-based sciatic nerve guidance channels implanted in rats after 8 weeks [24], polypyrrole-coated electrodes in rat brains after 3 or 6 weeks [25], or most pertinently, polypyrrole-based tissue scaffolds implanted in the coronary artery of rats after 5 weeks [26].…”
Section: Introductionmentioning
confidence: 94%
“…Studies have found that fibroblasts attached and grew well on the PPy nanoparticle-PLA composites with an increased viability when stimulated at currents of 10 -50 mA. This material retained biocompatibility in vivo even after maintaining electroconductivity for long periods of time (15% of conductivity retained after 1000 h; Wang, Z. et al 2003Wang, Z. et al , 2004Wang, X. et al 2004). Similarly, PANI -chitosan nanocomposites and PANI -gelatin cross-linked composites have been explored to increase biocompatibility and enhance surface characteristics.…”
Section: Physical -Chemical Modificationsmentioning
confidence: 99%
“…For example, in PPy-doped PSS, an uptake of positive ions such as Na þ from the medium is speculated to affect several cellular processes, including protein adsorption and the cell cycle (Wong et al 1994). PSS is widely used as a dopant in combination with PPy because of its relatively inert nature, its stability once deposited and biocompatibility upon implantation (Wang, X. et al 2004;Wang, Z. et al 2004). Other studies have also explored the modification of PPy via different dopants, including doping with dermatan sulphate for increasing keratinocyte viability (Ateh et al 2006), doping with heparin for increasing endothelial cell proliferation (Garner et al 1999a,b) and doping with laminin-derived peptides to control neuron and astrocyte adhesion (Stauffer & Cui 2006).…”
Section: Electrical Property Modificationmentioning
confidence: 99%
“…But all faced the same issue, which is that PPy is regarded as non-degradable. Even though the biodegradation behaviour and in vivo biocompatibility of poly(D,Llactide) (PDLLA)-PPy composites (similar to the composites used in the present study) have been evaluated by Wang et al [46,47], with the conclusion that the tissue reaction was not affected by the presence of PPy, the challenge remains to keep a sufficient conductivity at the lowest possible PPy concentration [11]. In parallel, research is being carried out on the synthesis of PPy-based polymers that would be inherently conductive and fully biodegradable, the difficulty being to maintain a conductivity that allows electronic applications [48].…”
Section: (A) Development Of New Biodegradable Conducting Materialsmentioning
confidence: 99%